Oscillation analysis in nonlinear differential equations with mixed neutral terms - Salma Aljawi; Fahd Masood; Omar Bazighifan (Applied Mathematics in Science and Engineering)
In this paper, we study the oscillatory properties of non-canonical neutral differential equations involving superlinear and sublinear terms. We adopt the Riccati technique with various substitutions to analyze the behavior of solutions and establish criteria that ensure their oscillation. The results expand upon previous studies by providing new results that enhance the mathematical understanding of non-canonical neutral equations, contributing to the development of oscillation theory for dynamical systems affected by time delays. We also provide three examples to demonstrate the applicability and importance of the results. The abstract was deliberately composed in a concise and focused manner in response to prior reviewer recommendations, aiming to highlight the main contributions of the study with clarity and precision. Its brevity is intentional to maintain coherence and avoid unnecessary elaboration. Nevertheless, if it is a strict requirement of the journal's formatting guidelines, we are prepared to revise the abstract accordingly to meet the word count criteria while ensuring that its academic value and clarity are preserved.